UNIVERSITY AGRICULTURAL STUDENTS’ INVOLVEMENT IN AGRIBUSINESS IN OSUN STATE, NIGERIA: PERCEPTIONAL ANALYSIS - ADELOYE, K. A.; OJO, K. O.; AFOLABI, A. A.; ABULUDE , I. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study assessed the perception of university agricultural students involved in agribusiness. Specifically, it determined the characteristics of students involved in agribusiness; their perception of the agribusiness in which they are involved; and their frequency of involvement.  A pretested and validated questionnaire and a focus group discussion guide were used to source quantitative and qualitative data respectively from 326 respondents selected through a two-staged sampling technique in Federal, State, and Private Universities in Osun State of Nigeria. Descriptive statistical techniques such as frequency counts and percentages were used to summarize the data, while Pearson Product Moment Correlation was used to test the hypothesis. The mean age and monthly income from agribusiness were 24.8±4.35 years and ₦12,775±7,119, respectively. Many (59.6%) of the respondents had an indifferent perception towards agribusiness. There was a significant relationship between the respondents’ involvement in agribusiness and their perception (r2 = 0.899) at a 0.01 level of significance. Also, at a 0.05 significance level, there was a significant relationship between university agricultural students’ perception of agribusiness and socio-economic characteristics such as age (r²= 0.115), and household and monthly income from agribusiness (r2= 0.336). The study then concluded that there was a significant relationship between the perception of agricultural students and their involvement in agribusiness. It was recommended that respondents should be oriented and enlightened on the need to be involved in agribusiness as empowerment while in school.